Analisis Faktor-Faktor Yang Memengaruhi Niat Berperilaku Pengguna Dalam Bertransaksi pada Online Travel Agent XYZ - Hadyan El Aufar; Ari Kusyanti; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-Commerce is all electronic information media that connects between organizations with external stakeholders (Dave, 2011). Since its inception in 2012, Online Travel Agent XYZ experienced several cases of cyber attacks committed by irresponsible people. An example is the theft of credit card information that befell a travel blogger and a ticket refund process by an unknown party. In this study, researchers conducted a test with multiple linear regression analysis method to determine what factors that affect the users's behavioral intention in transacting on Online Travel Agent XYZ. By using several models namely User Acceptance of Information Technology (UTAUT), User Information Internet Privacy Concern (IUIPC), and addition factor, privacy, security, and trust into this research. Variables that build the model in this study include: performance expectancy, effort expectancy, social influences, facilitating condition, control, awareness, privacy, security and trust. Data collection was done by distributing questionnaires and analyzed using multiple linear regression analysis. The results of the research which are the factors influencing the users's behavioral intention are trust, performance expectancy, and social influence.